Understanding Additives - Müller, Bodo (Vincentz Network, 2019)
This book covers everything about the mode of action, application and possible side effects of the most important coatings additives - in a single volume, presented in a textbook style. It reflects the needs of practical work - thus it enables the reader to rapidly gain a solid grounding in these critical, yet complex constituents of all paint formulations. It provides both an overview and in-depth basic knowledge of the most important classes of additives. The various types of damage eliminated or prevented by additives are vividly illustrated with colour photos. An indispensable companion for formulators!
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019)
Keywords: Adhesion promoters; Catalysts: driers, acid catalysts; Coalescing agents; Corrosion protection additives; Defoamers types and mode of action; Levelling agents; Neutralising agents; Photoinitiators/UV-initiators; Protection of coatings from weathering; Rheological active additives; Stabilisation of dispersions; Surface treatment; Wetting and dispersing agents; SCIENCE / Chemistry / General; Beschichtungsstoff; Additiv